MOODLE acceptance in distance education: an application of the UTAUT conceptual model (Revista Brasileira de Contabilidade e Gestão, 2014)
The Unified Theory of Acceptance and Use of Technology (UTAUT) model by Venkatesh et al. (2003) was applied in this research in order to verify the effects of influencing factors of Intention to Use and Real Use of the MOODLE platform in distance education. The research sample corresponds to 1.370 valid questionnaires, in a population of 300.000 subjects who use or have used MOODLE in Brazil. Data analysis was performed by structural equations modeling, generalized least squares and Jackknife resampling to identify the effect between variables. As the UTAUT requires many parameters, it was concluded that the model may be saturated. Low variability in responses suggests the execution of further investigations.
Keywords: conceptual model UTAUT; technology acceptance; IT Adoption